UPAYA PENINGKATAN HASIL BELAJAR BOLA VOLI MINI MELALUI PERMAINAN BONAS PADA SISWA KELAS IV SDN 02 BONDANSARI WIRADESA TAHUN PELAJARAN 2013/2014 - Aji Sidik; Mohamad Annas (Universitas Negeri Semarang, 2015)
This study aims to improve learning outcomes through audiovisual media handstand posture and consistency for high school students in the learning of Physical Education , Sport and Health . This study uses action research . In the implementation of the first cycle and second cycle meetings held 1 meeting . The subjects were a class XI Science SMAN 1 Sukorejo , District Sukorejo , Kendal . The instruments used in the data collection was obtained from observations at the time of learning , performance test and written test students . Based on the results obtained in the first cycle of learning outcomes that can meet the KKM as much as 31.4 % of the total number of students in the second cycle and increased to 82.9 % of the total number of students . Based on the above results , it can be concluded that the application of audiovisual media and consistency posture can improve learning outcomes handstand in class XI Science SMAN 1 Sukorejo . Expected for the Physical Education teacher at SMA N 1 Sukorejo to use audiovisual media and consistency in learning handstand posture